Faire descendre le maître de son piédestal. Retour sur parcours d’un formateur-chercheur - Philippe Glâtre (Éducation et Socialisation)
This paper takes a look back at my teaching career, traced through the eyes of the ignorant master, a figure proposed by Jacques Rancière in the light of the work of Joseph Jacotot. Whether in the context of accreditation of prior learning, competitive examination preparation or the fight against illiteracy, the aim is to question the place of knowledge and the relationship that fosters learner emancipation. Focusing on slam workshops and oral poetry projects carried out in Reunion Island as part of social work training courses, I show how the perspectives of Universal Teaching have inspired my practice, notably by inventing translingual moments, bringing the master down from his pedestal. This horizontalization of the relationship makes possible an inter-comprehension approach, used too little in language and culture didactics. Last but not least, equality of intelligence is achieved through projects in which students experience the field from a research perspective, giving knowledge back its democratic dimension.